Controlling necking in extrusion film casting using polymer nanocomposites - Rokade, Dhammaraj; Azad, Lal B.; Poddar, Suparna; Mishra, Satyendra; Pol, Harshawardhan V.; Shukla, Rishab (Journal of Macromolecular Science Part B-Physics, 2017)
The research described was concerned with the effect of layered-silicate-based organically modified nanoclay fillers on controlling the extent of necking in a polymer melt extrusion film casting (EFC) process. We show that a linear polythylene resin (such as a linear low-density polyethylene-LLDPE) filled with a very low percentage of well-dispersed (or intercalated) nanoclay displays an enhanced resistance to the necking phenomenon. In general, melt-compounded nanoclay-filled LLDPE resin formulations displayed a higher final film width (less necking), thus a lower final film thickness (greater draw down for the same draw ratio), and cooled down faster when compared to the base LLDPE resin. Incorporation of nanoclay filler in the mainly linear chain LLDPE resin led to significant modification of the melt rheological properties that, in turn, affected the melt processability of these formulations. Primarily, the intercalated nanoclay-filled LLDPE formulations displayed the presence of strain-hardening in unaxial extensional rheology. Additionally, the presence of well-dispersed nanoclay in the LLDPE resin led to a display of prominent extrudate swell indicating the presence of melt elasticity in such formulations. The presence of melt elasticity, as shown by shear rheology and strain-hardening, observed by uniaxial extensional rheology, contributed to the LLDPE nanoclay formulations displaying an enhanced resistance to necking for these films. It can be concluded that linear chain polymers susceptible to necking in an EFC process can be made more resistant to such necking by using nanoclay fillers at very low levels of loading.